Growth and development of Stevia rebaudiana Bert., in high and low levels of radiation - Alfredo Jarma-Orozco; Enrique Combatt-Caballero; Juan Jaraba-Navas (Current Plant Biology, 2020)
Stevia rebaudiana Bert., is a plant native to Paraguay that contains natural sweetener molecules, which, like growth, can be affected by environmental conditions. The solar radiation incident in the Colombian Caribbean is a stress factor for stevia crops because it can reach very high levels. This work aimed to evaluate the effect of low and high levels of radiation on the main growth rates of stevia. Biospace technology (BIOESP) was evaluated, which is based on the reduction of ultraviolet radiation. To achieve this, Stevia rebaudiana Bert. cv Morita II plants, were planted under BIOESP technology and compared to plants grown in direct solar radiation (DR). The main results indicated that photosynthesis can reach a point of light saturation close to 1200 μmol photosynthetically active radiation (PAR) m−2 s-1. The absolute and relative growth rates (AGR and RGR respectively) did not register differences in both environments. However, the net assimilation rate (NAR) and the harvest index (HI) showed greater efficiency in plants grown under BIOESP compared to those grown in the DR (NAR: 1.4 vs. 2.1 g m−2 d-1; HI: 0.54 vs. 0.62 % respectively). We conclude that BIOESP technology could be used as an efficient strategy of high radiation and temperature resilience caused by climate change in the Colombian Caribbean.